CORROSION DEFECT ANALYSIS OF GAS PIPELINE - Restining Tias, Vira
Natural gas is one of the most promising energy sources and is ranked as the third most widely used primary energy in Indonesia (20.31% of the national energy mix). One of the many important infrastructures in exploiting this potential is the piping system for distributing natural gas from one location to another. In this study, several analyses were carried out, namely pipe stress analysis based on ASME B31.8 and assessment of the corroded pipe based on ASME B31.G. First, the gas pipeline stresses will be calculated at each point and modeled using supporting software, that is, AutoPIPE, with the analysis criteria referring to ASME B31.8. Then, an assessment of the corroded pipe will be carried out and modeled using Abaqus software with the acceptance criteria referring to API FFS 579-1/ASME FFS-1. The analysis results on this Dayung Trunkline 24” gas pipeline, which has a length of ± 48 km and is buried underground, with 13 different corrosion anomaly locations at KM 17.864 – KM 17.901, meets the safety criteria based on codes and standards. The ASME B31.G level 3 assessment results indicate that the pipeline is still safe to be operated at an operating pressure of 8.27 MPa. This pipeline is also predicted to be allowed to operate for 17 months ahead with defects that occur and a corrosion rate of 0.11 mm/year.